Pengelolaan Sampah Organik Dengan Metode Puskoraling (Pupuk Kompos Ramah Lingkungan) Dalam Pemberdayaan Masyarakat Desa Domas - Muhammad Rafel Emirruso Mauluddin; Utari Esti Isnainazzahra; Syarief Hidajat (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The Domas Village area in Mojokerto Regency faces environmental cleanliness issues, particularly in waste management. These issues are tied to the Sustainable Development Goals (SDGs), specifically SDG 12 (Responsible Consumption and Production) and SDG 13 (Addressing Climate Change). This journal assesses a community empowerment program in Domas Village aimed at managing organic waste and converting it into compost raw materials. The program seeks to enhance the community's ability to manage waste efficiently and in an environmentally friendly manner through practical training and counseling. The research methodology involves a qualitative approach with an in-depth case study of the program. The findings demonstrate that this empowerment program can decrease the amount of organic waste being disposed of and provide additional income for the community through compost sales. It has also raised environmental awareness among villagers and encouraged active participation in waste management activities. This study concludes that community empowerment in Domas Village is an effective implementation of SDGs principles. To further develop this program, recommendations include expanding its reach to neighboring villages, improving access to waste processing technology, and strengthening collaboration between the government and the local community.